Characteristic features of choroidal nevus and small choroidal melanoma in Deep Range Imaging Optical Coherence Tomography - Markiewicz, Anna; Romanowska-Dixon, Bożena; Jakubowska, Barbara; Romanowska-Pawliczek, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2017)
Purpose : To determine characteristic features of choroidal nevi and small choroidal melanomas in Deep Range Imaging Optical Coherence Tomography in patients diagnosed and treated at the Department of Ophthalmology and Ocular Oncology of the Jagiellonian University, Medical College in Cracow within 2014 year. Material and methods : 71 patients with choroidal nevi or small choroidal melanomas were studied. Choroidal lesions were diagnosed clinically based on measurements of cross-sectional ultrasound images, mostly B-scans, and color fundus photography. The Topcon’s Deep Range Imaging Optical Coherence Tomography was used to enable better visualization of choroidal pathologies. Results : 11 patients were diagnosed with small choroidal nevus (<1.0 mm thickness and 5.0 mm diameter) and 13 – with small melanoma (according to Shields’ TFSOM rule). Deep Range Imaging Optical Coherence Tomography demonstrated characteristic features of these lesions: compression of choriocapillaris in all atypical nevi and small melanomas, inner and/or outer choroidal changes in all choroidal lesions. Other features, such as subretinal fluid, photoreceptors changes, macrophages with lipofuscin, were mostly present in atypical nevi and small melanomas. Dome tumor shape and wing border shape were found only in small melanomas. Conclusion : Deep Range Imaging Optical Coherence Tomography enables visualization of all choroidal structures and their pathology. It is useful in differential diagnosis of choroidal nevi and small choroidal melanomas.